Inequalities and stillbirth in the UK: a meta-narrative review - Claire Storey; Carol Kingdon; Soo Downe; Mark A Turner; Devender Roberts; Nicola Crossland; Kenneth William Finlayson (BMJ Open)
Objective To review what is known about the relationship between stillbirth and inequalities from different disciplinary perspectives to inform stillbirth prevention strategies.Design Systematic review using the meta-narrative method.Setting Studies undertaken in the UK.Data sources Scoping phase: experts in field, exploratory electronic searches and handsearching. Systematic searches phase: Nine databases with no geographical or date restrictions. Non-English language studies were excluded.Study selection Any investigation of stillbirth and inequalities with a UK component.Data extraction and synthesis Three authors extracted data and assessed study quality. Data were summarised, tabulated and presented graphically before synthesis of the unfolding storyline by research tradition; and then of the commonalities, differences and interplays between narratives into resultant summary meta-themes.Results Fifty-four sources from nine distinctive research traditions were included. The evidence of associations between social inequalities and stillbirth spanned 70 years. Across research traditions, there was recurrent evidence of the social gradient remaining constant or increasing, fuelling repeated calls for action (meta-theme 1: something must be done). There was less evidence of an effective response to these calls. Data pertaining to socioeconomic, area and ethnic disparities were routinely collected, but not consistently recorded, monitored or reported in relation to stillbirth (meta-theme 2: problems of precision). Many studies stressed the interplay of socioeconomic status, deprivation or ethnicity with aggregated factors including heritable, structural, environmental and lifestyle factors (meta-theme 3: moving from associations towards intersectionality and intervention(s)). No intervention studies were identified.Conclusion Research investigating inequalities and stillbirth in the UK is underdeveloped. This is despite repeated evidence of an association between stillbirth risk and poverty, and stillbirth risk, poverty and ethnicity. A specific research forum is required to lead the development of research and policy in this area, which can harness the multiple relevant research perspectives and address the intersections between different policy areas.PROSPERO registration number CRD42017079228.